Pengalaman Perilaku Konsumtif Gen Z Pada Komunitas Himalaya - Revinda Salsa Pitaloka; Nur’annafi Farni Syam Maella (PT Ilmu Data Indonesia, 2026)
The consumptive phenomenon is increasingly widespread among Gen Z, especially online shopping who are exposed to social media trends. This study aims to find out the experience of Gen Z consumptive behavior in the Himalayan community, understand consumptive communication behavior, and analyze the factors behind these consumptive behaviors. The research method used is an inductive qualitative approach through interviews and observations, which explores individual subjective experiences related to consumptive behavior. The object of the research from the title of Gen Z Consumptive Behavior Experience in the Himalayan Community is Consumptive Behavior. The results show that Gen Z's consumptive behavior in the Himalayan community is influenced by several consumptive behavior motives such as FOMO (Fear of Missing Out), lifestyle, confidence, and self-image. In addition, the factors behind this consumptive behavior include peer influence, self-desire, the role of social media advertising, and the attractiveness of promos, all of which reflect social interaction and individual motivation in purchasing decision-making. Consumptive communication behaviors are also found in interactions on social media platforms, where individuals recommend products to each other and share shopping experiences, which further encourages their consumptive behavior. However, this behavior often leads to impulsive spending, which can negatively impact financial and emotional well-being. Therefore, it is important to increase awareness among Gen Z about the consequences of uncontrolled consumptive behavior, so that they can be wiser in managing their finances and avoid social pressures that can trigger excessive spending. The research gap lies in the lack of longitudinal studies that explore Gen Z's changes in consumptive behavior over time and the impact of local culture, mental health, the effectiveness of financial education, as well as the variability of various social media platforms.